Tindak Tutur Asertif dalam Acara Catatan Mata Najwa Edisi “5 Pertanyaan Penting Buat yang Ogah Pemilu Ditunda” - Aini, Lutfiah; Jefiza, Iqbal; Vivi, Vivi (AHKAM, 2023)
Research on assertive speech acts is very important to study because speech is not just delivery. However, in the speech there is a purpose and purpose to be conveyed. This study aims to provide an overview to the reader so that they know assertive speech acts in the form of stating, reporting, and affirming in the responses of informants in the Mata Najwa program 5th edition of Important Questions for Those of You who are Averse to Postponed Elections. Assertive speech acts are speech acts that make the speaker become attached to the truth spoken. Types of assertive speech acts include explaining, stating, suggesting, showing and reporting. The type of research that the author uses is descriptive qualitative. This research was conducted in Mata Najwa's Notes edition 5 Important Questions for those of you who are averse to Postponed Elections. The data collection technique was carried out using recording, listening, and note-taking techniques. Data analysis used the matching method using referential sorting echnique. From the results of this study, assertive speech acts were obtained in the form of: stating, reporting, and affirming. Based on these results, obtained 17 forms of assertive speech acts, namely 7 assertive speech acts stating, 8 assertive speech acts reporting, and 2 asserting assertive speech acts.